Evaluation of the MISR fine resolution aerosol product using MODIS, MISR, and ground observations over China. (15th February 2020) - Si, Yidan; Chen, Liangfu; Xiong, Xiaozhen; Shi, Shuaiyi; Husi, Letu; Cai, Kun
Abstract: Recently, NASA's Multiangle Imaging SpectroRadiometer (MISR) team released the Version 23 (V23) 4.4-km Aerosol Optical Depth (AOD) product, which has better spatial resolution than V22 at 17.6 km. However, its quality has not been validated in China. Here, V23 products for different spatiotemporal domains are obtained for validation against Aerosol Robotic NETwork (AERONET) AOD measurements for 29 sites from 2008 to 2017. Based on the national daily mean, V23 AOD yields a correlation coefficient (R) of 0.902 with AERONET; 59.45% of retrievals fall within the expected error (=EE; ± 0.05  or  ± 0.2 × AOD ). A mean error (ME) of −0.0605 with 24.11% of retrievals falling below the EE indicates that MISR data are still underestimated at high AODs. The sample numbers and accuracies of spatially averaged 17.6-km and 50-km data are greatly improved relative to V22. The seasonal mean of V23 retrievals = EE in fall and winter are highest, followed by those in summer and spring; the validation results at 17.6 km are generally better than those at 50 km. By region, V23 retrievals = EE in the Beijing–Tianjin–Hebei (BTH), Yangtze River Delta (YRD) and Pearl River Delta (PRD) regions are 68.87%, 61.43%, and 73.13% respectively, while that of Taiwan is below 60% (55.75%). No V22 records exist in PRD, and V23 products over other regions in all seasons perform well; V22 retrievals in summer are also recommended. Compared with Terra/MODIS 3-km AOD in 2016, the V23 product has a slightly higher R value (0.925) with AERONET than MODIS (0.909). The MISR AOD bias is lower, and MODIS AOD is overestimated relative to the ground truth; both present consistent seasonality characteristics (spring > winter > summer > autumn), with the maximum in March and minimum in August. To investigate the spatiotemporal characteristics over long-term AOD, MISR V23 4.4-km AOD can be used in combination with other observation data. Highlights: Nationally, MISR V23 data are still underestimated with R = 0.902, EE = 59.45% and MAE = −0.0605. V23 retrievals = EE in the BTH, YRD and PRD regions are respectively greater than 55.75% in Taiwan. The V23 retrievals = EE in fall and winter are highest, followed by those in summer and spring. V23 products over BTH, YRD, Taiwan in all seasons perform well; that of V22 in PRD summer are better. MISR 4.4-km AOD biased lower and MODIS 3-km data overestimated relative to AERONET observations.